2022
DOI: 10.4102/sajim.v24i1.1496
|View full text |Cite
|
Sign up to set email alerts
|

Blood donor app usage behaviour and perceptions: Considerations for a blood donation app

Abstract: Background: South Africa often experiences critically low blood stock levels, making it vulnerable to blood shortages for everyday use and during times of crisis. There are over 3.5 billion smartphone users worldwide and, during 2019, app downloads were estimated at 204 billion. Considering that at least 51% of South Africans own a smartphone that can access the Internet and apps, it is clear that blood donation organisations in South Africa could benefit from engaging with the public through a mobile app.Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The growth of users is constant and sustainable and continues into 2022 which clearly differentiates it from COVID pandemic effects [14]. The donor acceptance according to feedback and store ratings is high and the adoption rate is above our expectations although comparison is difficult [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…The growth of users is constant and sustainable and continues into 2022 which clearly differentiates it from COVID pandemic effects [14]. The donor acceptance according to feedback and store ratings is high and the adoption rate is above our expectations although comparison is difficult [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, it is become a common practice nowadays, that in general, social media thru Internet-connected smart phones utilized maximally in every aspects of promoting, motivating, recruiting and even retaining blood donors [11,14,15]. According to Semaldi [15], donor motivation consists of three stage of development, which can be seen in Fig.…”
Section: Scientific Approach To Ensure Successful Blood Donationmentioning
confidence: 99%
“… 7 In fact, some studies have shown that using mHealth or mobile health applications can actually increase around 22.7% the number of appointments for donating blood, saving around 600,000 lives. 8 …”
Section: Introductionmentioning
confidence: 99%